Impact of fishing activities on different coralligenous assemblages of Gulf of Naples (Italy). (29th June 2017) - Ferrigno, Federica; Appolloni, Luca; Russo, Giovanni Fulvio; Sandulli, Roberto
Abstract : Coralligenous bioconstructions are among the most important Mediterranean habitats for biodiversity maintenance. However some characteristic and sensitive organisms, such as the fan corals, are considered endangered in the international community; indeed, they may be severely damaged by fishing activities causing mechanical damage and increasing sedimentation rate. ROV (Remotely Operated Vehicle) investigations were carried out in order to characterize different morphological types of coralligenous habitat (rim, bank and shoal) located in the southern Bay of Naples (Italy), and to assess the presence of lost fishing gears and their impact on these benthic communities. A rapid classification of different fishing pressures and impacts was obtained through the development of new, representative and synthetic categories. Image analysis revealed the presence of rich and diversified communities, characterized by several fan coral colonies. However, fishing activity dramatically affects these coralligenous habitats, entangling and covering benthic assemblages and leading to necrosis and to parasitic epibionts growth especially on branched organisms. Monitoring programmes may provide a detailed assessment of coralligenous habitats characterization, distribution and health status. An accurate evaluation of fishing pressure and impact may be considered a useful tool to improve sustainable management of these valuable habitats.